Allogeneic Hematopoietic Stem Cell Transplantation Mobilized With Pegylated Granulocyte Colony-Stimulating Factor Ameliorates Severe Acute Graft-Versus-Host Disease Through Enrichment of Monocytic Myeloid-Derived Suppressor Cells in the Graft: A Real World Experience - Li, Lin; Yin, Jin; Li, Yun; Wang, Chunyan; Mao, Xia; Wei, Jia; Cao, Yang; Wang, Na; Lin, Li; Xu, Jinhuan; Zhang, Yicheng (Frontiers in Immunology, 2021)
We compared the effectiveness and safety of pegylated granulocyte colony-stimulating factor (peg-G-CSF) vs. non-peg-G-CSF for hematopoietic stem cell mobilization in allogeneic hematopoietic stem cell transplantation in a real world setting. We included 136 consecutive healthy donors treated with non-peg-G-CSF (n = 53) or peg-G-CSF (n = 83), and 125 consecutive recipients (n= 42 and 83, respectively) in this study. All harvesting was completed successfully. No significant difference in leukapheresis number and adverse events frequency was observed, nor were there severe adverse events leading to discontinuation of mobilization. The leukapheresis products mobilized by peg-G-CSF had higher total nucleated cells (p < .001), monocytic myeloid-derived suppressor cells (p < .001), granulocytic myeloid-derived suppressor cells (p = .004) and B cells (p = .019). CD34+ cells and other lymphocyte subsets (T cells, regulatory T cells, natural killer [NK] cells, etc.) were similar in both apheresis products. Patients who received grafts mobilized by peg-G-CSF exhibited a lower incidence of grade III-IV acute graft-versus-host disease (p = .001). The 1-year cumulative incidence of chronic graft-versus-host disease and relapse, 1-year probability of graft-versus-host disease-free relapse-free survival, and overall survival did not differ significantly between subgroups. Our results suggest that collecting allogeneic stem cells after the administration of peg-G-CSF is feasible and safe. Peg-G-CSF mobilized grafts may reduce severe acute graft-versus-host disease compared with non-peg-G-CSF mobilized grafts after allogeneic stem cell transplantation. The beneficial effects of a peg-G-CSF graft might be mediated by increased numbers of monocytic myeloid-derived suppressor cells.